Avaliação em larga escala: participação do aluno público alvo da educação especial - Benini, Ana Lia (2017)
The policy for large scale evaluation and the policies for an inclusive school education have been widely discussed and put into practice by researchers and educators, being target of criticism and problematizations, once they create implications in the school environment. Therefore, this piece of research aimed at establishing relations between the large scale evaluation and the participation of students who are target of Special Education, and the objective was to know and analyze the participation of these students at Prova Brasil. The methodology chosen was the qualitative approach from the studies of Ludke and André (1986) and Neves (1996), besides counting on the contributions of authors like Maturana and Varela (2011) and Vasconcellos (2002). In order to produce the data, we have used observations (GIL, 2009) during the carrying out of Prova Brasil in the year of 2015, and we have also carried out interviews (LUDKE; ANDRÉ, 1986) with the regular class’s teachers whose groups depict students who are target of Special Education and the Special Education teacher of each school. The analytical production of data happened using the content analysis (BARDIN, 2011). It is possible to affirm that the participation of students who are target of Special Education in the large scale evaluations predicted the presence of a monitor to help during the carrying out of the test Prova Brasil, however, this action was taken by the Special Education teachers. The students had more time to finish the test (thirty minutes), but still they were not able to finish it in the due time, therefore they had to check the answers randomly in the answer sheet. In addition to that, the students reported being tired throughout the test, and needed successive interruptions to go to the toilet and drink water. Concerning the participation of these students in the large scale evaluations, the teachers pointed out the need of adaptations in the evaluative tool, which can be carried out by the school, by the teachers, once these are the ones who know the students’ needs. The teachers believe the adaptation could be an alternative to guarantee more fidelity for a learning mensuration of students who are target of Special Education in large scale evaluations. From a general perspective, the processes of large scale evaluation have provoked changes in the everyday school life, especially regarding the preparation for the tests and the concern to improve or keep up the results at Index of Development of Basic Education (IDEB). The teachers and managers are being impelled to think in sample tests and general tests also directed to students who are target of Special Education aiming the keep up or improvement of Index of Development of Basic Education (IDEB) results.